STRATEGI KOMUNIKASI PEMASARAN TERPADU MEDIA BISNIS INDONESIA PERWAKILAN PEKANBARU DALAM MENINGKATKAN PENGGUNAAN JASA EVENT - Arie Gunawan; Ringgo Eldapi Yozani; Lie Othman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the implementation of Integrated Marketing Communication (IMC) in enhancing event service sales at Harian Bisnis Indonesia Representative Pekanbaru. It aims to analyze how IMC is applied not only as a coordination mechanism of promotional tools but also as a relational and strategic communication system that supports long-term relationships with event sponsors. A qualitative method was used through in-depth interviews, observation, and documentation to explore the integration of advertising, public relations, sales promotion, and personal selling in marketing communication practices The findings show that IMC operates as a multilevel communication system. Advertising functions as the initial stage in building awareness and cognitive positioning of audiences. Public relations strengthens credibility through media legitimacy and third-party endorsement. Sales promotion accelerates perceived value through bundled offerings and integrated marketing solutions, while personal selling serves as the main interpersonal channel that enables negotiation, trust-building, and co-creation of value between the organization and sponsors.The study also finds that IMC implementation is not linear but cyclical and adaptive, where each communication touchpoint contributes to continuous relationship building and value creation. In addition, the integration of the marketing mix 7P demonstrates that IMC is operationalized across product, price, place, promotion, people, process, and physical evidence, reflecting a holistic communication system in the service industry. In conclusion, IMC at Bisnis Indonesia Pekanbaru functions as a relational communication system that goes beyond promotional effectiveness to foster trust, commitment, and sustainable partnerships with stakeholders. This study contributes to IMC literature by highlighting its shift from a transactional promotional framework to a strategic system of value and relationship creation